2020
DOI: 10.1371/journal.pone.0227795
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence and determinants of modern contraceptive utilization among women in the reproductive age group in Edaga-hamus Town, Eastern zone, Tigray region, Ethiopia, June 2017

Abstract: Introduction All individuals and couples have a basic human right to decide freely and responsibly the number, spacing, and timing of their child. However, In Ethiopia, the prevalence of contraceptive utilization remains low and it varies in different regions. Therefore, this study was aimed to determine prevalence and determinant factors affecting the utilization of modern contraception in the reproductive age group (15-49 years) in Edaga-Hamus Town. Methodology A community based Cross-Sectional study was car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 18 publications
2
14
1
Order By: Relevance
“…Our study shows that negotiation on contraception with a sexual partner may ultimately lead to a decreased FCU during sexual activities among males and females. Such negative impact on FCU might be largely attributed to males, as previous studies have reported that males' attitudes largely influence females' decision in contraceptive use during sexual activities, either in positive or negative directions under different scenarios [19][20][21]. In addition to males, our findings further imply that females also tend to bring down the FCU while having sex with males.…”
Section: Discussionsupporting
confidence: 65%
“…Our study shows that negotiation on contraception with a sexual partner may ultimately lead to a decreased FCU during sexual activities among males and females. Such negative impact on FCU might be largely attributed to males, as previous studies have reported that males' attitudes largely influence females' decision in contraceptive use during sexual activities, either in positive or negative directions under different scenarios [19][20][21]. In addition to males, our findings further imply that females also tend to bring down the FCU while having sex with males.…”
Section: Discussionsupporting
confidence: 65%
“…It might also be due to the fact that mothers who use modern contraception have long experience with healthcare services where they have been frequently for the specified service and that might made them a bit more knowledgeable than those who are not using. This might implied that increasing modern contraceptive utilization might trigger co-utilization of other services like CS [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…There were differences in the mix of modern contraception methods by sociodemographic characteristics such as educational attainment, place of residence, religion, caste, and wealth status [ 5 , 10 , 11 ]. However, permanent contraception methods have been found to have different patterns than the two remaining modern methods of contraception in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, developing countries adopted a mix of contraception methods that includes Short-Acting Reversible Contraception (SARC 1 ), Long-Acting Reversible Contraception (LARC) and permanent contraception, which can probably be an alternative family planning strategy to meet the high unmet need for modern contraception [9]. Previous research suggested that providing a wide range of mixed contraceptive methods might increase the contraceptive prevalence and lead to better family planning [10,11]. Studies in developing countries indicated that countries with more access to different methods of contraception (i.e.…”
Section: Introductionmentioning
confidence: 99%